Neonatal outcomes in In vitro fertilization (IVF) pregnancies - Muhammad Buchori; Suryono Yudha Patria; Tunjung Wibowo; Ita Fauzia Hanoum (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
small-for-gestational age (SGA), and low birth weight (LBW) rates are approximately twiceas high in IVF pregnancies than in natural pregnancies. The IVF procedures have becomemore routine in recent years in Indonesia, but there have been few assessments ofneonatal outcomes. The study aimed to evaluate the risk of preterm birth, SGA, and LBWin IVF infants. This was a retrospective cohort study performed in Dr. Sardjito GeneralHospital, Yogyakarta from January 2012 to December 2016. Pre-coded questionnaireswere used to collect data from medical records. The relative risk of preterm birth, SGA,and LBW among IVF infants were calculated and compared to naturally conceived infants.A total sampling method was used for the IVF infants and a simple random samplingmethod was used for naturally conceived infants, who were born on the same day as aninfant in the IVF group.A total of 108 infants were recruited, consisting of 54 IVF infants and 54 naturallyconceived infants. The IVF infants had increased risk of preterm birth (RR = 2.0; 95%CI0.52 - 7.58) and LBW (RR = 1.25; 95%CI 0.53 - 2.92). However, the IVF infants didnot have an increased risk of SGA (RR = 1.0; 95%CI 0.21 - 4.73). In conclusion, therisk of preterm birth and LBW in IVF infants are higher than in naturally conceived infants,but not statistically significant. However, there is no increased risk of SGA in IVF infants.